2021
DOI: 10.21037/tlcr-20-1020
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin expression status is a potential biomarker for brain metastasis development in EGFR-mutant NSCLC patients

Abstract: Background: Despite advances in systemic therapy and improvements in survival for advanced epidermal growth factor receptor (EGFR) mutant non-small cell lung cancer (NSCLC), brain metastasis (BM) remains a poor outcome. Previous studies on risk factors for BM occurrence included unselected patients and biomarker prediction of BM in these populations were not well studied. We aimed to identify the role of epithelial mesenchymal transition (EMT) marker and clinical factors predicting BM in EGFR-mutant NSCLC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Second, the number of samples with enough tissue available to perform IHC was less than expected, and third, some tumor samples were quite old, which could modify the IHC results. However, in relation to this issue, the percentage of Vimentin expression observed in our samples is consistent with that reported in previous studies [ 113 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Second, the number of samples with enough tissue available to perform IHC was less than expected, and third, some tumor samples were quite old, which could modify the IHC results. However, in relation to this issue, the percentage of Vimentin expression observed in our samples is consistent with that reported in previous studies [ 113 ].…”
Section: Discussionsupporting
confidence: 93%
“…High levels of Vimentin were associated with lower PFS in our cohort of patients ( Figure 12 b). Previous studies observed that high expression of Vimentin was associated with a poor outcome to first generation EGFR-TKI and the development of brain metastasis in EGFRm NSCLC patients [ 113 , 114 ]. Our findings also revealed that non-expression of CD133 was associated with a poor degree of histological differentiation, progression to the disease, distant metastasis ( Figure 11 ), and a low OS ( Figure 12 a).…”
Section: Discussionmentioning
confidence: 99%
“…and chronic lung diseases (IPF, autoimmune ILDs, COPD, and asthma) ( Li et al, 2017a ; Musaelyan et al, 2018 ; Nissen et al, 2019 ; Surolia et al, 2019 ; Li et al, 2021 ). Additionally, vimentin is a gold-standard marker of epithelial–to-mesenchymal differentiation during malignancies ( Satelli and Li, 2011 ; Bogush et al, 2020 ), and is also proposed as a diagnostic and prognostic marker in lung cancers ( Rho et al, 2009 ; Dauphin et al, 2013 ; Rodriguez et al, 2013 ; Havel et al, 2015 ; Teocharoen et al, 2021 ).…”
Section: Vimentin Intermediate Filaments In Pathological Roles In Lun...mentioning
confidence: 99%
“…Although no direct anti-vimentin molecule is approved for the treatment of any lung disease, there are several clinical trials utilizing interventions that decrease the expression of vimentin. The value of amplified expression of vimentin is recognized as a prognostic marker is critical in non-small cell lung cancer (NSCLC) ( Al-Saad et al, 2008 ; Dauphin et al, 2013 ; Ye et al, 2016 ; Teocharoen et al, 2021 ). The expression levels of vimentin were used as a prognostic indicator for the treatment efficacy for patients with NSCLC with erlotinib, erlotinib/bevacizumab (EB) or cisplatin/gemcitabine/bevacizumab (PGB) ( Richardson et al, 2012 ; Villalobos et al, 2019 ).…”
Section: Vimentin As a Biomarker And As A Drug Target For The Lung Di...mentioning
confidence: 99%
“…NSE, histological type, number of metastatic lymph nodes, and tumor grade were used to construct a nomogram for use in brain metastasis prediction (18). Vimentin expression was also identified as a potential predictor of brain metastasis in EGFR -mutant NSCLC patients (19).…”
Section: Introductionmentioning
confidence: 99%